Study on Understanding the Use of Light Fire Extinguishers in Airport Terminals - Yeti Komalasari; Faiz Muzhaffar Nafri Gumay; Sukahir Sukahir; Parjan Parjan (Journal of Innovation in Educational and Cultural Research, 2024)
Emergencies and conditions can occur at any time. Preventive measures are necessary to reduce accidents and emergencies. This research, which measures the level of understanding of tenant employees regarding the use of light fire extinguishers in airport terminals, is of significant importance. The study used a mixed methods research approach with a sample of 77 people and obtained measurable values for tenant employees' understanding of light fire extinguishers. The results included 87% of tenant employees understanding emergencies, 81.8% knowing the meaning of light fire extinguishers, 55.8% knowing how to use light fire extinguishers, 58.4% who have never participated in socialization on light fire extinguishers use, and 83.1% who did not have a certificate/license for using light fire extinguishers, provide a crucial basis for further policy-making. In the form of preventive actions, these policies will be carried out by aircraft rescue and fire fighting in the form of fire prevention outreach/training through educational innovations in using light fire extinguishers via videos accessed by all tenant employees. The success of these actions will be measured through pre/post-test results before and after the material intervention, with certificates issued to participants who meet the assessment scoring. As part of the airport community, active participation in these initiatives is not just crucial but also a responsibility and a testament to the ownership of the safety of all airport users.